2011
DOI: 10.3109/10428194.2011.582907
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of productive immunoglobulin heavy chain gene rearrangements in childhood acute lymphoblastic leukemia

Abstract: We analyzed the CDR3 region of 80 children with B-cell acute lymphoblastic leukemia (B-ALL) using the ImMunoGeneTics Information System and JOINSOLVER. In total, 108 IGH@ rearrangements were analyzed. Most of them (75.3%) were non-productive. IGHV@ segments proximal to IGHD-IGHJ@ were preferentially rearranged (45.3%). Increased utilization of IGHV3 segments IGHV3-13 (11.3%) and IGHV3-15 (9.3%), IGHD3 (30.5%), and IGHJ4 (34%) was noted. In pro-B ALL more frequent were IGHV3-11 (33.3%) and IGHV6-1 (33.3%), IGHD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
1
5
1
Order By: Relevance
“…However, our study results differed from previous reports, which have shown that 40% and 21% of IGH rearrangements result in productive rearrangements [1420]. However, our results correlate with a study of 108 IGH sequences from 80 children with precursor B-ALL, which revealed that 75.3% of them were unproductive [22]. …”
Section: Discussioncontrasting
confidence: 97%
“…However, our study results differed from previous reports, which have shown that 40% and 21% of IGH rearrangements result in productive rearrangements [1420]. However, our results correlate with a study of 108 IGH sequences from 80 children with precursor B-ALL, which revealed that 75.3% of them were unproductive [22]. …”
Section: Discussioncontrasting
confidence: 97%
“…ALL is considered to originate from pre-B cells, which are aberrantly blocked at the transition to immature B cells. This mechanism explains the unmutated or low-mutated status due to lack of SHM, the high frequency of unproductive IGH rearrangements due to continuously active recombinase enzyme, and the initiation of IGK/IGL rearrangements that go against allelic exclusion rules due to improper in-frame selection [ 40 , 41 , 47 , 59 ]. Clonal evolution can’t be ignored in ALL and likely occurs by continuing rearrangement processes (successive VH to DJH or secondary rearrangements) [ 40 , 41 ] and selection pressure mediated by treatments [ 60 ].…”
Section: The Oncogenesis Of B-lineage Malignancies and The Correspond...mentioning
confidence: 99%
“…This mechanism explains the unmutated or low-mutated status due to lack of SHM, the high frequency of unproductive IGH rearrangements due to continuously active recombinase enzyme, and the initiation of IGK/IGL rearrangements that go against allelic exclusion rules due to improper in-frame selection [ 40 , 41 , 47 , 59 ]. Clonal evolution can’t be ignored in ALL and likely occurs by continuing rearrangement processes (successive VH to DJH or secondary rearrangements) [ 40 , 41 ] and selection pressure mediated by treatments [ 60 ]. Measurements of the IG gene repertoire exhibited biased VH usage toward VH3 and VH1 families, most frequently involving the VH6-1, VH1-2, VH3-11, VH3-13, and VH3-15 segments.…”
Section: The Oncogenesis Of B-lineage Malignancies and The Correspond...mentioning
confidence: 99%
See 1 more Smart Citation
“…Some gene mutations or rearrangements are responsible for the development of aggressive and treatment-resistant types of leukemia. [12][13][14][15][16] Patients with ALL should be screened for the following genetic aberrations: deletion of IKZF1, PAX5, CDKN2A, CDKN2B, P2RY8-CRLF2, EGR, rearrangements of ABL1, ABL2, CSF1R, PDGFRbeta, IGH, CRLF2, EPOR, NTRK3, BCR-ABL1, AFF1 (mll), AFF1-KMT2A (MLL-AF4), ETV6-RUNX1 (TEL-AML1), TCF3, mutation of JAK2, as well as hypo-or hyperdiploidy. 9 Detection of the genetic background that contributes to poor prognosis remains a challenge and may be a basis for developing new therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%